The dangers in our trail of digital breadcrumbs. (January 2015) - Stretton, Tracey; Aaron, Luke
Abstract : What do Apple, eBay, Snapchat, Target and LinkedIn have in common? All of you with accounts at any of the aforementioned companies should know the answer to the question, as you will have likely been asked to change your password in the recent past, or at least read about it in the news. With varying degrees of exposure (in some cases quite literally) the users of these services have all suffered some form of data breach in recent history. We all leave a huge amount of personal data online. And while we might worry about it being misused, in some situations the digital breadcrumbs left behind by a user are extremely useful. Tracey Stretton and Luke Aaron of Kroll Ontrack take a look at the kinds of personal data and evidence of our activities that we leave in our wake and suggest some basic measures that both individuals and businesses can take to lessen the potential impact of inappropriate use.